Petroleum geology-related sites in and around Miri, Sarawak, Malaysia: potential geotourism resources - Adriansyah, D.; Ulfa, Y.; Amalina Binti Ahmad Ramdzani, Illiya; King-King, T. (Oradea University Press, 2016)
This paper discusses the petroleum geology-related sites in and around Miri, in the state of Sarawak, Malaysia and their potentials as geotourism resources. Desk study was conducted by reviewing some literatures related to the topic and the study area. A field visit was conducted in May 2014 to observe the recent situation of all sites in details. There are some geological/natural and man-made features in and around the city which are closely related to petroleum geology. The Canada hill (anticline), a unique tectonic feature which emerged from the surrounding coastal plain, is a petroleum trap and used to be the location of many oil wells. On top of this hill is the location of the first oil well (called "the Grand Old Lady") and Miri Petroleum Museum. The deltaic sandstone outcrops of Miri Formation (such as the Airport Road outcrop and other outcrops around Miri) are very ideal outcrops of sandstone reservoirs. Oil seeps, mud volcanoes, and oil sands are some evidences of petroleum occurrences in and around the city. Niah Caves can be seen as an analogue of carbonate reservoirs. All these sites and features can attract people to visit the city, not only geologists and geology students who want to study the petroleum geology of Miri area, but also the common people who are interested in such a field.